IMPLEMENTATION OF STATE SOCIAL POLICY OF UKRAINE IN TERMS OF REFORMING PUBLIC AUTHORITIES - Korotych O.B. (Pressing Problems of Public Administration, 2016)
Implementation of state social policy in Ukraine is facing a number of problems, some of which are new, additional challenges associated exclusively with the present conditions that aggravate the social, political, and financial instability. In this regard, a systemic reform of public authority in Ukraine deserves special attention.